(untitled) (Journal of Computational Mathematics, 2000)
After giving the representation of moment generating function for the S-03bb type random variable by solving a differential equation, we prove that this type random variable is of regular n-r order moment. Furthermore, we establish the higher order asymptotic formula for generalized Feller operators by making use of the generalized Taylor formula.